2019
DOI: 10.1039/c9ta07857f
|View full text |Cite
|
Sign up to set email alerts
|

Sulfurization-induced edge amorphization in copper–nickel–cobalt layered double hydroxide nanosheets promoting hydrazine electro-oxidation

Abstract: The electrocatalytic hydrazine oxidation reaction (HzOR) has drawn extensive attention due to its high energy conversion efficiency and wide applications in hydrazine-assisted water splitting and direct hydrazine fuel cells (DHFC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 55 publications
1
53
0
Order By: Relevance
“…45,46 Meanwhile, the concentration of Ni 3+ species with P-NiFeP/Ni is higher than that of Ni 2 P/Ni, which further reveals Fe-doping increase the unsaturation of Ni ions. 17 It is remarkable that the high-valence species enrichment can better promote electro-oxidation reactions 47,48,17, which helps to improve H z OR performance. In the Fe 2p spectrum of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 Meanwhile, the concentration of Ni 3+ species with P-NiFeP/Ni is higher than that of Ni 2 P/Ni, which further reveals Fe-doping increase the unsaturation of Ni ions. 17 It is remarkable that the high-valence species enrichment can better promote electro-oxidation reactions 47,48,17, which helps to improve H z OR performance. In the Fe 2p spectrum of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] Therefore, it is imperative to choose a candidate that is more readily oxidation than OER to reduce energy wastage. Among many alternative OER (oxidation of methanol, 12 ethanol, 13 benzyl alcohol, 14 pentahydroxymethyl furfural (HMF), 15 urea, 16 and hydrazine, 17,18 etc. ), hydrazine oxidation reaction (H z OR) possesses ultra-low theoretical overpotential, single product, and safe environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…Surface sulfurization functionalized copper‐nickel‐cobalt ternary layered double hydroxides for HzOR with improved activity and durability has been reported by Liu et al [139] . The optimal ratio of ternary metal ions significantly affected the electronic structure and thereby HzOR activity and kinetics.…”
Section: Ni‐based Hzor Electrocatalysts: Merits Characterization Andmentioning
confidence: 89%
“…DFT calculations were also carried out to gain detailed information about the HzOR catalytic reactivity of CoNiÀ RÀ S (Ni 3 Co 6 S 8 ). [63] The estimated density of state for the Ni 3 Co 6 S 8 exhibited a semiconducting property and the energy bandgap was much lower than that of NiCo 2 O 4 counterpart, manifesting the enhanced charge mobility within the adopted Surface sulfurization functionalized copper-nickel-cobalt ternary layered double hydroxides for HzOR with improved activity and durability has been reported by Liu et al [139] The optimal ratio of ternary metal ions significantly affected the electronic structure and thereby HzOR activity and kinetics. The improved performance of the hybrid arisen from the combined features of enriched active species, enhanced charge transfer, and preferable reaction kinetics.…”
Section: Other Ni-transition Metals Based Hzormentioning
confidence: 94%
“…Furthermore, Asset et al reported that NiMo/C catalyst prepared via wet impregnation process method, exhibited better catalytic activity compared to Ni/C catalyst [30]. Liu et al reported that the ternary CuNiCo LDH nanosheet array catalyst prepared via sulfurization-induced edge amorphization exhibited good catalytic activity and power durability [31]. The catalysts and maximum peak values compiled from the literature studies for hydrazine electrooxidation were given in Table 1.…”
Section: Introductionmentioning
confidence: 99%